2012
DOI: 10.1016/j.ejvs.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability of Sodium Tetradecyl Sulphate (STD) and Polidocanol Foam: Impact on Vein Damage in an In-vitro Model

Abstract: Although polidocanol foam shows greater stability than STD foam perhaps remaining in the vein for longer, endothelial cell loss and damage to the media were significantly greater with STD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…Despite this, only one of these studies elaborates on the ability of the sclerosant to penetrate into the media. 18 This work showed damage in the media layer in veins treated with sclerotherapy and suggested a direct penetration effect. Our study demonstrates a decrease in endothelial and SMC markers that was most intense at the endothelium, but maintained in the media.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite this, only one of these studies elaborates on the ability of the sclerosant to penetrate into the media. 18 This work showed damage in the media layer in veins treated with sclerotherapy and suggested a direct penetration effect. Our study demonstrates a decrease in endothelial and SMC markers that was most intense at the endothelium, but maintained in the media.…”
Section: Discussionmentioning
confidence: 72%
“…19 In 2012, McAree et al studied the stability of foams made using STS and POL and noted the superior penetration and damage to the media caused by STS over POL. 18 While this work showed that the sclerosant had a detrimental morphological effect on the media, the information given was restricted to tissue damage demonstrated only by standard haematoxylin and eosin staining. No information was presented by the authors for the cause of this damage and it was assumed that it was directly caused by the penetration of STS into the media.…”
Section: Introductionmentioning
confidence: 93%
“…Mc Arree et al[17] konnten zeigen, dass Polidocanol zwar einen Endothelschaden verursacht, dieser jedoch inkomplett ist. Ein inkompletter Thrombus mit erhaltenen Endothelinseln könnte eine Rekanalisation hervorrufen.…”
unclassified
“…Because the vein itself exists reflux, and the gas foam has certain air embolism, it makes the gas foam being difficult to move into the deep vein with the blood flow in the varicose vein, and the sclerosing agent can cause the endothelial cells damage, vasospasm, formation of mural thrombus, vascular closure, eventually formation of fibrous cord and gradually soften (15)(16)(17). The mixture of the gas itself may reduce the dosage of the destructive sclerosing agent and increase the contact area of the sclerosing agent with the vessel wall (18), while ultrasound guided sclerotherapy enable the injection more safe and accurate, and reduce the complication.…”
Section: Discussionmentioning
confidence: 99%